Impact of technology-integrated innovative assessment methods on Chinese tertiary students’ academic achievement / Meng Wu ... [et al.] - Meng, Wu; Subramaniam, Geetha; Sidhu, Gurnam Kaur; Li, Cailing; Zhu, Linling; Li, Lin (Universiti Teknologi MARA, 2024)
In today’s global shift towards formative assessment, technology-integrated innovative assessment methods have become the call of the day. This is especially true in a majority of the postpandemic online teaching and learning environments that are supported by innovative information and communications technology (ICT) solutions. The main aim of this study was to assess the impact of technology-integrated innovative assessment methods on 70 Chinese tertiary students’ academic achievement in a private university located in Shanghai, China. The study involved two stages, i.e., an experimental research design and a survey design. In the experimental design, assessment tasks in the experimental group were based on technology-integrated innovative assessment methods, whilst the control group was assessed based on traditional-based assessment methods. For the survey, data was collected using a survey questionnaire wherein the data analysis employed mean and standard deviation and Partial least squares (PLS). The experimental results revealed that students belonging to the experimental group performed academically better than the control group’s students in the end-ofmodule examination. Furthermore, findings from the survey showed that technology acceptance, platform usability, and assessment convenience moderately influenced performance expectancy. Besides, while higher cumulative grade point average (CGPA) levels correlated with a stronger relationship between assessment convenience and performance expectancy, lower CGPA levels correlated with a stronger relationship between technology acceptance and performance expectancy. The findings in this study imply that educators must embrace and integrate technology-integrated innovative assessment methods to enhance educational quality, which is in line with SDG 4, with an ultimate aim to optimize student learning experiences in an increasingly technology-driven educational environment.